2016
DOI: 10.1155/2016/2853543
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctional Activities of Equisetum ramosissimum Extract: Protective Effects against Oxidation, Melanoma, and Melanogenesis

Abstract: Equisetum ramosissimum, a genus of Equisetaceae, is a medicinal plant that can be separated into ethyl acetate (EA), dichloromethane (DM), n-hexane (Hex), methanol (MeOH), and water extracts. EA extract was known to have potent antioxidative properties, reducing power, DPPH scavenging activity, and metal ion chelating activity. This study compared these five extracts in terms of their inhibiting effects on three human malignant melanomas: A375, A375.S2, and A2058. MTT assay presented the notion that both EA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 34 publications
(39 reference statements)
2
40
0
Order By: Relevance
“…The ultraviolet (UV) rays are one of the known causes of melanoma [6]. Our skin has the ability to protect us from exterior factors, controls body temperature, and stores water and fat.…”
Section: Journal Of Food Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The ultraviolet (UV) rays are one of the known causes of melanoma [6]. Our skin has the ability to protect us from exterior factors, controls body temperature, and stores water and fat.…”
Section: Journal Of Food Qualitymentioning
confidence: 99%
“…For assays of the reducing power ability of the extract, different concentrations ranges of each tea extract were mixed with 85 L of 67 mM sodium phosphate buffer (pH 6.8) and 2.5 L of 20% K 3 Fe(CN) 6 to investigate the reducing powers of the extracts. The mixture was kept at 50 ∘ C for 20 min and centrifuged for 10 min at 3,000 .…”
Section: Reducing Powermentioning
confidence: 99%
“…Equisetum arvense and Lentinus edodes are probably responsible for the improvement of BAP associated with the decrease in d-ROMs in the experimental group as compared to C. Experimental outcomes reported byLi et al (2016) showed that Equisetum spp. is considered an antioxidant ingredient due to its ability to reduce free radical chain reactions.…”
mentioning
confidence: 90%
“…In the current studies it was demonstrated that the accumulation of ROS decreased organism salubrity because the oxidative damage was a contributor to the senescence . Aging is a natural process for everyone, evoking various diseases, and skin is highly responsive to photo‐aging due to oxidative stress created by ROS . Reactive oxygen species induced by UVB damage to cellular DNA, RNA, proteins, and lipids in theory contributes to the physiology of aging.…”
Section: Introductionmentioning
confidence: 75%
“…1,2 Aging is a natural process for everyone, evoking various diseases, and skin is highly responsive to photo-aging due to oxidative stress created by ROS. 5 Reactive oxygen species induced by UVB damage to cellular DNA, RNA, proteins, and lipids in theory contributes to the physiology of aging. Due to skin aging caused by internal and external factors, most people have more than one skin disorder after the age of 65 years.…”
Section: Introductionmentioning
confidence: 99%